Blood Markers of Coagulation, Fibrinolysis, Endothelial Dysfunction and Inflammation in Lacunar Stroke versus Non-Lacunar Stroke and Non-Stroke: Systematic Review and Meta-Analysis - Wiseman, Stewart; Marlborough, Fergal; Doubal, Fergus; Webb, David J.; Wardlaw, Joanna (Cerebrovascular diseases (Basel, Switzerland), 2014)
Background: The cause of cerebral small vessel disease is not fully understood, yet it is important, accounting for about 25% of all strokes. It also increases the risk of having another stroke and contributes to about 40% of dementias. Various processes have been implicated, including microatheroma, endothelial dysfunction and inflammation. A previous review investigated endothelial dysfunction in lacunar stroke versus mostly non-stroke controls while another looked at markers of inflammation and endothelial damage in ischaemic stroke in general. We have focused on blood markers between clinically evident lacunar stroke and other subtypes of ischaemic stroke, thereby controlling for stroke in general. Summary: We systematically assessed the literature for studies comparing blood markers of coagulation, fibrinolysis, endothelial dysfunction and inflammation in lacunar stroke versus non-stroke controls or other ischaemic stroke subtypes. We assessed the quality of included papers and meta-analysed results. We split the analysis on time of blood draw in relation to the stroke. We identified 1,468 full papers of which 42 were eligible for inclusion, including 4,816 ischaemic strokes, of which 2,196 were lacunar and 2,500 non-stroke controls. Most studies subtyped stroke using TOAST. The definition of lacunar stroke varied between studies. Markers of coagulation/fibrinolysis (tissue plasminogen activator (tPA), plasminogen activator inhibitor (PAI), fibrinogen, D-dimer) were higher in lacunar stroke versus non-stroke although fibrinogen was no different to non-stroke in the acute phase. tPA and PAI were no different between lacunar and non-lacunar stroke. Fibrinogen and D-dimer were significantly lower in lacunar stroke compared to other ischaemic strokes, both acutely and chronically. Markers of endothelial dysfunction (homocysteine, von Willebrand Factor (vWF), E-selectin, P-selectin, intercellular adhesion molecule-1 (ICAM), vascular cellular adhesion molecule-1 (VCAM)) were higher or had insufficient or conflicting data (P-selectin, VCAM) in lacunar stroke versus non-stroke. Compared to other ischaemic stroke subtypes, homocysteine did not differ in lacunar stroke while vWF was significantly lower in lacunar stroke acutely [atherothrombotic standardized mean difference, SMD, -0.34 (-0.61, -0.08); cardioembolic SMD -0.38 (-0.62, -0.14)], with insufficient data chronically. Markers of inflammation (C-reactive protein (CRP), tumour necrosis factor-alpha (TNF-α), interleukin-6 (IL-6)) were higher in lacunar stroke versus non-stroke, although there were no studies measuring TNF-α chronically and the sole study measuring IL-6 chronically showed no difference between lacunar stroke and non-stroke. Compared to other ischaemic stroke subtypes, there was no difference (CRP) or insufficient or conflicting data (TNF-α) to lacunar stroke. IL-6 was significantly lower [atherothrombotic SMD -0.37 (-0.63, -0.10); cardioembolic SMD -0.52 (-0.82, -0.22)] in lacunar stroke acutely, with insufficient data chronically. Key Messages: Lacunar stroke is an important stroke subtype. More studies comparing lacunar stroke to non-lacunar stroke specifically, rather than to non-stroke controls, are needed. Prospective studies with measurements taken well after the acute event are more likely to be helpful in determining pathogenesis. The available data in this review were limited and do not exclude the possibility that peripheral inflammatory processes including endothelial dysfunction are associated with lacunar stroke and cerebral small vessel disease.